Colective elementary excitations of bose-einstein condensed two-dimensional magnetoexcitons strongly interacting with electrom-hole plasma - Moscalenco, Sveatoslav; Dumanov, Evgheni; Podlesnîi, Igor; Boţan, Victor; Liberman, Michael (Moldavian Journal of the Physical Sciences, 2005)
The collective elementary excitations of a system of Bose-Einstein condensed two-